Theme of Love in Odes Published in Daily Jang Quetta in 2014 - Abdul Waheed (Al-Burz, 2019)
Daily Jang, Quetta is an esteem Urdu newspaper of Baluchistan. Besides publishing local, National and international news for the information of general public, it is also contributing a major portion of Urdu Literature to the readers. A special weekly edition is published purely for literary writings which include Prose, Poetry and many other literary genres. In poetry, Ode has been given full coverage. A critical analysis of these Odes, being published in Daily Jang has many aspects in their subject. Those poets, who exercised the theme of love in their Odes in 2014 “Fikr-o-Adab” edition, are critically examined. The objective of this study is to find out the love theme in the Odes of these poets.